Thoughts of Fazlur Rahman Education and Its Contribution to The Development of Islamic Education Theory - Fathonah, Parisaktiana (Universitas Islam Negeri Raden Mas Said Surakarta, 2018)
This study aims to discuss the thoughts of education Fazlur Rahman and its contribution to the development of Islamic education theory today. Data collection used documentation method. The collected data sources serve as documents. The documents are then read and understood to find the necessary data in accordance with the formulation of the problems that exist in this study. After the necessary data is considered sufficient, systematized for further analysis. Fazlur Rahman as one of the reformers in Islamic education contributes by offering a more emphasis on development strategies in areas that are part of the education system itself, as well as integrating the two sciences, in order to avoid disintegration in education, so that there is no gap between the sciences -science. The idea of Rahman in the renewal of Islamic education, which is about the purpose of education, education system, learners, educators, educational facilities, and Islamic education curriculum.